12-Deoxyphorbol-13-Hexadecanoate Abrogates OVX-Induced Bone Loss in Mice and Osteoclastogenesis via Inhibiting ROS Level and Regulating RANKL-Mediated NFATc1 Activation - He, Qi; Yang, Junzheng; Chen, Delong; Li, Yejia; Gong, Dawei; Ge, Hui; Wang, Zihao; Wang, Haibin; Chen, Peng (Frontiers in Pharmacology, 2022)
Osteoporosis is a major health problem in the elderly. Almost every bone can fracture due to the increased bone fragility in osteoporosis which poses a major challenge to public health. 12-deoxyphorbol-13-hexadecanoate (DHD), one of the main bioactive components of Stellera chamaejasme L. (Lang Du), is considered to have anti-tumor, antibacterial and anti-fungal properties. However, the role of DHD in osteoporosis is still elusive. In this study, we demonstrated for the first time that DHD inhibits the receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclastogenesis and bone resorption in a dose- and time-dependent manner without exhibiting cytotoxicity in vitro. Mechanistically, we found that DHD not only represses the expression of osteoclast marker genes by suppressing RANKL-induced mitogen-activated protein kinase (MAPK) and calcium signaling pathways but also scavenges reactive oxygen species (ROS) through enhancing cytoprotective enzymes expression. Furthermore, DHD inhibits the activation of nuclear factor of activated T cells 1 (NFATc1) during RANKL-induced osteoclasts formation. Preclinical studies revealed DHD protects against bone loss in ovariectomy (OVX) mice. In sum, our data confirmed that DHD could potentially inhibit osteoclastogenesis by abrogating RANKL-induced MAPK, calcium, and NFATc1 signaling pathways, as well as by promoting the expression of ROS scavenging enzymes, thereby preventing OVX-induced bone loss. Thus, DHD may act as a novel therapeutic agent to manage osteoporosis.